Perancangan Aplikasi Konsultasi Kesehatan Mental - Santosa, Mochammad Kevin; Sihananto, Andreas Nugroho (Universitas PGRI Semarang, 2022)
Abstract—Health does not only include physical health also includes mental health. Lack of insight into mental health make people less aware of the importance of mental health duet o limited access to mental health services. Public awareness of mental health is also quite low. The rate of mental health ilness is also quite high in Indonesia. Information on suicide prevention hotlines is also very limited. This problem was obtained through a research process on several respondents. Therefore, the authors take this case study as a solution on these problems. By creating a mobile-based interface design to provide education and also make it easier for the public to get services,suicide prevention hotline, and online seminars on mental health. With these features, we hope to be able to answer these problems.